The role of FOXA family transcription factors in glucolipid metabolism and NAFLD - Yu, Chuchu; Li, Xiaojing; Zhao, Yu; Hu, Yiyang (Frontiers in Endocrinology, 2023)
Abnormal glucose metabolism and lipid metabolism is a common pathological process in many metabolic diseases, such as nonalcoholic fatty liver disease (NAFLD). Many studies have shown that the forkhead box (FOX) protein subfamily FOXA has a role in regulating glucolipid metabolism and is closely related to hepatic steatosis and NAFLD. FOXA exhibits a wide range of functions ranging from the initiation steps of metabolism such as the development of the corresponding metabolic organs and cell differentiation, to multiple pathways of glucolipid metabolism, to end-of-life problems of metabolism such as age-related obesity. The purpose of this article is to review and discuss the currently known targets and signal transduction pathways of FOXA in glucolipid metabolism. To provide more experimental evidence and basis for further research and clinical application of FOXA in the regulation of glucolipid metabolism and the prevention and treatment of NAFLD.